Radiographer reporting of neurological magnetic resonance imaging examinations of the head and cervical spine: Findings of an accredited postgraduate programme. Issue 4 (November 2018) - Piper, K.; Pittock, L.; Woznitza, N.
Abstract: Introduction: To analyse the objective structured examination (OSE) results of the first cohorts of radiographers (n = 13) who successfully completed an accredited postgraduate programme in clinical reporting of neurological magnetic resonance imaging (MRI) examinations of the head and cervical spine. Methods: Forty MRI examinations were used in the OSE which included a range of abnormal cases (prevalence of abnormal examinations approximated 50%) and included: haemorrhage, infarction, demyelination disease, abscess, mass lesions (metastatic deposits, meningioma, glioma, astrocytoma); and disc disease, cord compression, stenosis, ligament rupture, syringomyelia appearances on patients referred from a range of referral sources. Normal variants and incidental findings were also included. True/false positive and negative fractions were used to mark the responses which were also scored for agreement with the previously agreed expected answers based on agreement between three consultant radiologists' reports. Results: The mean sensitivity, specificity and agreement rates for all head and cervical spine investigations (n = 520) combined were 98.86%, 98.08% and 88.37%, respectively. The highest scoring cases were cases which included astrocytoma, disc protrusion with cord compression and glioma. The most common errors were related to syringomyelia, ligament rupture and vertebral fracture. Conclusions: These OSE results suggest that in an academic setting, and following an accredited postgraduate education programme, this group of radiographers has the ability to correctly identify normal MRI examinations of the head/cervical spine and are able to provide a report on the abnormal appearances to a high standard. Further work is required to confirm the clinical application of these findings. Highlights: Following accredited training, radiographers can report MRI examinations of the head or cervical spine to a high standard. The accuracy of the radiographers' reports is similar to rates in other MRI reporting studies of the lumbar spine or knee. Radiographers in an academic setting, can report to a similar standard to non-specialised consultant radiologists.